2020
DOI: 10.2174/1745017902016010024
|View full text |Cite
|
Sign up to set email alerts
|

Online Romance Scams: Relational Dynamics and Psychological Characteristics of the Victims and Scammers. A Scoping Review

Abstract: Background: Digital communication technologies can overcome physical, social and psychological barriers in building romantic relationships. Online romance scams are a modern form of fraud that has spread in Western societies along with the development of social media and dating apps. Through a fictitious Internet profile, the scammer develops a romantic relationship with the victim for 6-8 months, building a deep emotional bond to extort economic resources in a manipulative dynamic. There are two not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 28 publications
0
24
0
7
Order By: Relevance
“…It is well-established that personality pathology represents an individual vulnerability factor which can predict an increased risk for any type of crime [ 1 3 ]. Prevalence rates of diagnoses of personality disorders range between 42 and 78% in prisoners (e.g., [ 4 ]), being much higher than the rates usually observed in the general population, i.e., 4–13% [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-established that personality pathology represents an individual vulnerability factor which can predict an increased risk for any type of crime [ 1 3 ]. Prevalence rates of diagnoses of personality disorders range between 42 and 78% in prisoners (e.g., [ 4 ]), being much higher than the rates usually observed in the general population, i.e., 4–13% [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bank Negara Malaysia juga terlibat sebagai rakan strategik di samping badan bukan kerajaan (NGO) dan kumpulan pemimpin masyarakat (KKMM 2019). Manakala Coluccia et al (2020) pula mencadangkan jalinan hubungan rakan strategik seperti institusi undang-undang dan perkhidmatan kesihatan mental juga perlu diambil kira sebagai strategi pembangunan protokol penyelidikan. Pusat penjagaan kesihatan mental perlu menggunakan alat saringan pemantau risiko jenayah cinta siber bagi membantu mangsa yang mengalami gangguan psikologi dan memerlukan bantuan klinikal.…”
Section: Rumusanunclassified
“…Psychiatric disorders play an important role as well. Schizophrenia and bipolar disorder ( Carabellese et al, 2012 ; Pozza et al, 2019 , 2020 ) and mood and personality disorders ( Dunsieth et al, 2004 ; Coluccia et al, 2020 ) were detected in sex offenders. In their research on a sample of 1346 sex offenders, Eher et al (2019) found that 50.1% of them suffered from personality disorders.…”
Section: Introductionmentioning
confidence: 99%